2020
DOI: 10.1101/2020.01.22.915355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The logic of containing tumors

Abstract: Challenging the paradigm of the maximum tolerated dose, recent studies have shown that a strategy aiming for containment, not elimination, can control tumor burden more effectively in vitro, in mouse models, and in the clinic. These outcomes are consistent with the hypothesis that emergence of resistance to cancer therapy may be prevented or delayed by exploiting competitive ecological interactions between drug-sensitive and resistant tumor cell subpopulations. However, although various mathematical and comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 35 publications
6
30
0
Order By: Relevance
“…We have shown that high initial tumour cell density, and low initial resistance fractions, maximise the benefit of adaptive therapy, assuming a cure is not possible. This prediction is consistent with previous non-spatial [11,15,16,18,22,33] and spatial theoretical studies [11,19], and experimental evidence in cancer [11] and bacteria [34].…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that high initial tumour cell density, and low initial resistance fractions, maximise the benefit of adaptive therapy, assuming a cure is not possible. This prediction is consistent with previous non-spatial [11,15,16,18,22,33] and spatial theoretical studies [11,19], and experimental evidence in cancer [11] and bacteria [34].…”
Section: Discussionsupporting
confidence: 92%
“…). As Hansen et al[8] and Viossat and Noble[32] show, if one accounts for potential de novo resistance acquisition, this high burden can generate situations in which maintaining a pool of sensitive cells can in fact accelerate the emergence of the resistant population. Investigating the risks associated with the higher average tumour burden under adaptive therapy is an important area of future research.…”
mentioning
confidence: 99%
“…This criterion was implemented in the first clinical trial of adaptive therapy for castrateresistant prostate cancer (20). Would a less aggressive treatment stop criterion be better as suggested by more recent models (27,28,34)? We simulated a suite of adaptive therapy simulations with a new stopping criterion of 20% reduction to address this question.…”
Section: A Different Treatment-stopping Criterionmentioning
confidence: 99%
“…Strobl et al showed how the turnover rate of cancer cells within the tumor influences benefits derived from adaptive therapy (27). More general and deeper mathematical analysis by Viossat and Noble predict the clinical benefits of tumor containment therapy (28).…”
Section: Introductionmentioning
confidence: 99%